Analisis Pengaruh Jarak dan Diameter Lubang Rivet Terhadap Kekuatan Sambungan Tumpuk Beban Aksial - Rizky Juliardi; Oleh Oleh; Iwan Nugraha Gusniar (Jurnal Ilmiah Wahana Pendidikan, 2022)
Beam splicing using butt joints is one of the most common forms of connection found in the construction of bridges, towers or other structures. The size of the connection used is adjusted to the ability of the base material, the existing external load and the material of the seam and rivet itself. The number of rivets used must also be adjusted to the load to be supported. If the number of rivets used is too much, it will also cause stress on the connection itself. Due to the complicated combination of the two elements, namely the seam and the diameter of the rivet used, everyone can determine the size at will regardless of the stress propagation on the seam or rivet. In this study, the authors analyzed the effect of the combination of hole diameter and the distance between holes on the strength of the connection at stack connection. Based on the results of research that has been carried out on a double blade seam plate with variations in the thickness of the seam and the diameter of the rivet. The maximum stress that occurs on the seam or rivet is smaller than the stress on the main plate. So the possibility of failure is greater on the main plate. For rivets with a diameter of 12 mm and a seam thickness of 6 mm, the maximum stress that occurs is still below the main plate stress. At the rivet diameter of 16 mm, the stress began to increase sharply on the main plate and the seam. The decrease in the cross- sectional area due to the increase in the diameter of the rivet increases the stress generation. For connection and rivet safety factors, the average is above 7 and the condition is very safe. This safety factor is also greatly influenced by the distance between the holes and the thickness of the seam plate used. The greater the decrease in the normal surface area, the lower the safety factor.